2017
DOI: 10.1021/acs.est.7b05050
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Effects of the Antibiotic Tetracycline on Transcriptional Responses of Daphnia magna and Its Relationship to Higher Levels of Biological Organizations

Abstract: Given the risk of environmental pollution by pharmaceutical compounds and the effects of these compounds on exposed ecosystems, ecologically relevant and realistic assessments are required. However, many studies have been mostly focused on individual responses in a single generation exposed to one-effect concentrations. Here, transcriptional responses of the crustacean Daphnia magna to the antibiotic tetracycline across multiple generations and effect concentrations were investigated. The results demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 74 publications
0
4
0
2
Order By: Relevance
“…In fact, it is now known that most antibiotics, regardless of their receptors and modes of actions, provoke considerable transcription activation at low concentrations in bacteria and multicellular organisms alike [33,156]. Kim and colleagues found that tetracycline exposure affected gene regulation in D. magna , mostly impacting the general stress response, as well as protein and carbohydrate metabolism [192]. Moreover, such changes in gene transcription level can carry-over over multiple generations even in the absence of tetracycline [192], thus potentially impacting on animal population even after the removal of the molecule from the environment.…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is now known that most antibiotics, regardless of their receptors and modes of actions, provoke considerable transcription activation at low concentrations in bacteria and multicellular organisms alike [33,156]. Kim and colleagues found that tetracycline exposure affected gene regulation in D. magna , mostly impacting the general stress response, as well as protein and carbohydrate metabolism [192]. Moreover, such changes in gene transcription level can carry-over over multiple generations even in the absence of tetracycline [192], thus potentially impacting on animal population even after the removal of the molecule from the environment.…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%
“…Kim and colleagues found that tetracycline exposure affected gene regulation in D. magna , mostly impacting the general stress response, as well as protein and carbohydrate metabolism [192]. Moreover, such changes in gene transcription level can carry-over over multiple generations even in the absence of tetracycline [192], thus potentially impacting on animal population even after the removal of the molecule from the environment.…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%
“…Esta investigación, informa sobre el efecto en la descendencia (en dos generaciones sucesivas) donde parentales y descendencia fueron sometidos a la acción de antibióticos en la etapa larval, específi camente estado larva II de la cepa silvestre "santiago" de Drosophila melanogaster. Estudios anteriores realizados con Daphnia magna informaron de efectos trans-generacionales sobre los individuos y las poblaciones de esta especie sometida a la acción de tetraciclinas, en cuatro generaciones sucesivas (Kim et al 2017(Kim et al , 2014, atribuyendo este efecto transgeneracional a la redistribución del gasto metabólico (Kim et al 2012).…”
Section: Discussionunclassified
“…Los machos tratados con el antibiótico, cruzados con hembras no tratadas producen exceso de machos en la descendencia y reducción de la aptitud reproductiva del macho, lo que se manifi esta en una condición de movilidad espermática reducida en padres y heredada por sus hijos en Drosophila melanogaster (Zeh et al 2012;Yang & Lu 2011) también demostrada en vertebrados, incluyendo al hombre (Elzeinova et al 2013;Hargreaves et al 1998). Efectos multigeneracionales de oxitetraciclina sobre Daphnia magna demostraron que induce diferentes respuestas transcripcionales dependientes de las dosis aplicadas y la generación considerada lo que afecta al metabolismo (Kim et al 2017).…”
Section: Discussionunclassified
“…As a result, antibiotics have been detected in most aquatic environments such as wastewater [ 3 ], surface water [ 4 ], groundwater [ 5 ] and even drinking water [ 6 , 7 ], as well as in many soil environments such as manure, soil and sediments [ 8 , 9 , 10 , 11 ]. Residual antibiotics can not only bring various direct damages to the plants and animals living in contaminated water or soil environment [ 9 , 12 , 13 , 14 , 15 ] but also break the original microbial community structure or even the ecosystem functions or enzymatic activity of bacteria [ 16 , 17 , 18 ]. Thus, finding an economic and environmentally friendly degradation method for these contaminates is crucial.…”
Section: Introductionmentioning
confidence: 99%